Navigating Challenges and Potential Solutions to Address Contentious Topics in the School Setting. Insights From Teachers and School Leaders for Fostering Constructive Dialogue and Mitigating Classroom Polarisation. Case Studies From the Project ‘Participation’ - Lauretta, Davide (Italian Sociological Review, 2025)
This article reports the specific challenges, contentious topics, and potential good practices for handling risks of toxic polarisation of pupils in the secondary school environment, as experienced by a sample of teachers and school leaders as part of their work with students in six EU countries: Belgium, Greece, Italy, Poland, Romania, and The Netherlands. Data and findings have been collected through explorative research in the field, within the framework of the H2020 Project named ‘PARTICIPATION’. Adolescence is a period of life where pupils are in an ongoing process of construction and consolidation of their identity and values, and school represents a microcosm of society (Haldane, 2004) where different worldviews coexist and can be in contrast. For this reason, training teachers to educate students in democratic values and developing critical thinking and resilience to violence and intolerance are fundamental to preventing toxic polarisation. To present the main issues and potential solutions identified during this research path, this article undertakes a cross-country analysis based on the interaction with the involved groups through the Social Lab methodology.